The Earliest Settlement in Southern Sweden - Late Paleolithic Settlement Remains at Finjasjön, in the North of Scania - Larsson, Lars (Current Swedish Archaeology, 1994)
Our knowledge of Late Palaeolithic settlements in Southern Sweden has been increased significantly by investigations which started at the end of the 1980s. Great interest attaches to the new find locations discovered close to lake Finjasjön in the north of Scania. Two find locations have been investigated at the outlet of the river Almeån from the lake. The Vångamossen bog is a camping place dating from the Bromme Culture. Finds recovered from a sandy hill at Mölleröd indicate brief visits including during the Hamburg Culture. This find location is the first to contain remains from the Hamburg Culture in Sweden. New studies into the changes which took place in the Öresund area during the ice melting phase point to the existence of a land bridge only for short periods. The outflow of meltwater through the Öresund at other times during the Late Glacial period prevented or obstructed the fauna migration routes. These factors must be taken into account in any comparison of Late Palaeolithic settlement in Southern Sweden with the various cultural complexes which occur in North Germany and in the Danish region.